Rapid Assessment of the Potential Paucity and Price Increases for Suggested Medicines and Protection Equipment for COVID-19 Across Developing Countries With a Particular Focus on Africa and the Implications - Sefah, Israel Abebrese; Ogunleye, Olayinka O.; Essah, Darius Obeng; Opanga, Sylvia A.; Butt, Nadia; Wamaitha, Annie; Guantai, Anastasia Nkatha; Chikowe, Ibrahim; Khuluza, Felix; Kibuule, Dan; Nambahu, Lahya; Abubakar, Abdullahi Rabiu; et al. (Frontiers in Pharmacology, 2021)
Background: Countries across Africa and Asia have introduced a variety of measures to prevent and treat COVID-19 with medicines and personal protective equipment (PPE). However, there has been considerable controversy surrounding some treatments including hydroxychloroquine where the initial hype and misinformation lead to shortages, price rises and suicides. Price rises and shortages were also seen for PPE. Such activities can have catastrophic consequences especially in countries with high co-payment levels. Consequently, there is a need to investigate this further. Objective: Assess changes in utilisation, prices, and shortages of pertinent medicines and PPE among African and Asian countries since the pandemic. Our approach: Data gathering among community pharmacists to assess changes in patterns from the beginning of March until end of May 2020. In addition, suggestions on ways to reduce misinformation. Results: 131 pharmacists took part building on the earlier study in Bangladesh. There were increases in the utilisation of antimicrobials especially in Nigeria and Ghana, which was mainly antimalarials. There were limited changes in Namibia and Vietnam reflecting current initiatives to reduce inappropriate prescribing and dispensing of antimicrobials. Encouragingly, there was increased use of vitamins/ immune boosters across the studied countries as well PPE where documented. In addition, generally limited change in the utilisation of herbal medicines. However, shortages have resulted in appreciable price increases in some countries although moderated in Pakistan through government initiatives. Suggestions in Namibia going forward included better planning and educating patients. Conclusion: Encouraging to see increases in utilisation of vitamins/ immune boosters and PPE. However, concerns with increased utilisation of antimicrobials needs addressing alongside misinformation, unintended consequences from the pandemic and any appreciable price rise. Community pharmacists and patient organisations can play key role in providing evidence-based advice, helping moderate prices through improved stock management, and helping address unintended consequences of the pandemic.